Signification functions of Undomestic Goddess novel cover - Cindy Maria Christine Pandie; Ahmad Jum’a Khatib Nur Ali (EduLite: Journal of English Education, Literature and Culture, 2022)
Novel cover is like human appearance; it is the first thing that the people will take notice of. It turned out that novel cover is quite essential in influencing the opinions and impression of the reader regarding the novel itself. Novel’s cover using symbols, fonts, and colors, construct cover signs functions. The researcher intends to analyze the novel covers sign functions. The source data of the research is selected using purposive sampling following the standard of a novel cover. This research uses three (3) covers of the novel Undomestic Goods by Sophie Kinsella as the data source. The theory of signification by Rolland Barthes is the analytical tool of this research used to determine the function of the elements in the object of research. The results of the study are both covers have their own significations functions; the first edition (1) cover function emphasizes on promoting the novel by using signification content of the novel. Cover (2) emphasizes promotion function using the author popularity and best-selling author status and promoting the novel by using signification content of the novel. Cover three (3) the latest edition function emphasizes on ‘advertises’ the novel by using the author popularity and best-selling author status.